1996
DOI: 10.4148/0146-9282.1425
|View full text |Cite
|
Sign up to set email alerts
|

Technology Leadership: Ten Essential Buttons for Understanding Technology Integration in the 21st Century.

Abstract: This article serves to provide the framework for understanding the ingredients of successful technology integration in public schools. The "ten button" format of this article is the guiding document for understanding each of the subsequent articles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There was a positive correlation in the effective use of technology in the classroom. Bailey (2000) stated the essential elements for understanding technology integration and leadership in the 21st century. Bailey stated what technology leaders need to know concerning technology integration, such as change, curriculum, ethics, infrastructure, safety and security, staff development, teaching/learning, technology planning, technical support, and technology leadership.…”
Section: Uğur and Koç -Leading And Teaching With Technologymentioning
confidence: 99%
“…There was a positive correlation in the effective use of technology in the classroom. Bailey (2000) stated the essential elements for understanding technology integration and leadership in the 21st century. Bailey stated what technology leaders need to know concerning technology integration, such as change, curriculum, ethics, infrastructure, safety and security, staff development, teaching/learning, technology planning, technical support, and technology leadership.…”
Section: Uğur and Koç -Leading And Teaching With Technologymentioning
confidence: 99%
“…Research indicates that teachers need considerable support to integrate technology into the curriculum, including a nurturing work environment that provides opportunities for teachers to take risks and collaborate with one another (Bailey, 1996). MacNeil and Delafield (1998) argued that a faculty that becomes more comfortable with the ideas of technology will more easily integrate it into the curriculum.…”
Section: What Promising Practices In the Area Of Technology Does Cartmentioning
confidence: 99%
“…Support from principals is crucial in determining whether teachers will integrate technology into their classrooms. This support requires that principals have basic technology skills and standards from which to work (Bailey 1997). As well as this, principals need to provide leadership by creating a vision, sharing the vision, acquiring funding, planning and coordinating the process of introducing technology, developing the curriculum, training, and setting the technology standards that will provide the basis for administrators' knowledge (Banoğlu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Competencies can be both observable and non-observable. Bailey (1997) Cakir (2012) showed that school administrator, who has the primary responsibility for technology integration in the schools, and computer teachers, who play an important role in the integration of technologies in the classroom, need to have a great interest in and a highly positive attitude towards technology integration.…”
Section: Introductionmentioning
confidence: 99%